Miocene orographic uplift forces rapid hydrological change in the southern central Andes - Rohrmann, Alexander (2016)
Rainfall in the central Andes associated with the South American Monsoon and the South American Low-Level Jet results from orographic effects on atmospheric circulation exerted by the Andean Plateau and the Eastern Cordillera. However, despite its importance for South American climate, no reliable records exist that allow decoding the evolution of thresholds and interactions between Andean topography and atmospheric circulation, especially regarding the onset of humid conditions in the inherently dry southern central Andes. Here, we employ multi-proxy isotope data of lipid biomarkers, pedogenic carbonates and volcanic glass from the Eastern Cordillera of NW Argentina and present the first long-term evapotranspiration record. We find that regional eco-hydrology and vegetation changes are associated with initiation of moisture transport via the South American Low-Level Jet at 7.6 Ma, and subsequent lateral growth of the orogen at 6.5 Ma. Our results highlight that topographically induced changes in atmospheric circulation patterns, not global climate change, were responsible for late Miocene environmental change in this part of the southern hemisphere. This suggests that mountain building over time fundamentally controlled habitat evolution along the central Andes.